Keanekaragaman Makro-invertebrata di Pantai Sepanjang, Gunungkidul, DI. Yogyakarta - Saputra, Alanindra (Prosiding KPSDA, 2015)
Macroinvertebrates is one of bioindicator for aquatic ecosystem. By assessing indicator species, diversity, functional groups of macroinvertebrates community, it is possible to determine water quality. Purpose of this research was to inventory and study the macroinvertebrates species diversity in Sepanjang Beach, Gunungkidul, Yogyakarta. This research was conducted on Wednesday, November 25th 2014 at Sepanjang Beach, Gunungkidul, Yogyakarta. Sampling points was determined by line transect method. At each transect, sampling with 1x1 m2 plots was done. The data obtained in this study was the result of macro-invertebrates species inventory in each sampling point and the number of individuals of each species. Data analysis was performed by calculating the Shannon-Weiner diversity index (Hâ). Result of this research showed that there were 63 macroinvertebrates species with 1033 number of individuals found in Sepanjang beach. Result of calculation of Shannon-Weiner diversity index (Hâ) showed the diversity index of macro-invertebrates in Sepanjang beach was 1.24. The diversity index showed that the diversity index of macro-invertebrates in Sepanjang beach categorized by medium diversity.